A Novel Handover Control Strategy Combined with Multi-hop Routing in LEO Satellite Networks - Duan, Chaofan; Feng, Jing; Chang, Haotian; Song, Bin; Xu, Zhikang (2018 IEEE International Parallel and Distributed Processing Symposium Workshops (IPDPSW), 2018)
To maintain satellite communication continuity, satellite handover is an important topic in Low Earth orbit (LEO) satellite system. Based on the deep study of LEO satellites motion and inter-satellite visibility, a position-based minimum delay strategy (PMDS) is proposed for Walker Star satellite constellation with inter-satellite links. This strategy is a distributed processing method and it is based on the position information of both users and selects the 'nearest' satellite as the access satellite when handover occurs. This strategy makes full use of the characteristics of the Walker Star constellation and taking into account the impact of routing, solves the handover issue between different satellites effectively. The simulation of propagation delay under different handover strategies are obtained by the Network Simulator version 2 (NS2). The results show that the proposed strategy can reduce the propagation delay while keeping the handover times acceptable and maintain a lower complexity.